The Relationship of Age and Parity of Pregnant Women in Trimester III With Completeness of Tetanus Toxoid Immunization at Klinik Fera in 2021 - Susi Amenta Beru Perangin Angin; Faradita Wahyuni; Pratiwi Lumbantobing; Yuni Vivi Santri Purba (Pena Cendekia Insani, 2022)
Tetanus Toxoid (TT) immunization is a weakened and purified tetanus germ toxin that is given to infants, children and mothers in an effort to provide protection against tetanus (Rinaldi, 2016). The research design used was an analytical study with a cross sectional study approach, aiming to determine the relationship between age and parity of third trimester pregnant women with the completeness of tetanus toxoid immunization at the Fera Clinic in 2021. The number of samples in this study was 30 people. With accidental sampling technique. Data collection instrument in the form of a questionnaire used to obtain chi square data. The results of this study indicate that there is no significant relationship between maternal age and TT immunization with p value = 0.171 (P > 0.05). There is a significant relationship between maternal education and the provision of TT immunization, with p value = 0.013 (P <0.05). There was no significant relationship between maternal parity and TT immunization with p value = 0.083 (P > 0.05). It is expected that health workers (midwives and nurses) in conducting counseling activities, age affects a person's knowledge so that an individual approach is needed to explain the importance of TT immunization.